Functional Properties of Composite Flours Produced From Blends of Fermented Maize (Zea mays L) And Fermented Soybean (Glycine max) Flour (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
The objective of this study was to determine the functional properties of composite flours produced from blends of fermented maize (Zea mays L) and fermented soybean (Glycine max) flour. Maize grains were sorted, cleaned, fermented for 48 h, oven dried (60 °C to constant weight), milled to flour and then sieved (250 μm) to produce maize flour. The soybean was sorted, cleaned, boiled, cooled, dehulled, and fermented for 48 h with Rhizopus oligosporus (0.4g per 100g of soybean), oven dried (60 °C to constant weight), milled and sieved (250 μm) to produce fermented soybean flour. Using mixture design, maize and soybean flour samples were blended in the ratios 90:10, 80:20, 70:30, 60:40, and 50:50 to obtain composite flours while 100% maize flour and 100% soybean flour served as controls. Functional properties of the samples were evaluated. Inclusion of fermented soybean to fermented maize flour significantly (p
Keywords: Flour; Functional properties; Maize; Rhizopus oligosporus; Soybean